ISOLATION AND IDENTIFICATION OF BACTERIA FROM SHRIMP POND AS BIOREMEDIATION AGENT CANDIDATE TO REDUCE TOXIC AMMONIA - Amalia Rachma Fatchiyyah; Haeruddin Haeruddin; Ervia Yudiati (Saintek Perikanan : Indonesian Journal of Fisheries Science and Technology, 2021)
The accumulation of ammonia in shrimp pond is one major problem that leads to production failure. Ammonia can disturb the metabolic balance of the shrimps and making them more susceptible to disease. An approach to overcome a poor water quality in shrimp culture caused by ammonia is introduced bacteria as a bioremediation agent. The utilization and the development of the local bioremediation agent are expected to be a solution to improve water quality. This study aimed to isolate and identify bacteria from traditional shrimp pond as candidate to reduce ammonia. Bacteria were isolated in liquid enrichment medium. Bacteria identification was done through biochemical tests also molecular analysis of the 16S rRNA gene sequence using primer 27F and 1492R and phylogenetic analysis using MEGA 6.0 program. The results showed that as many as three bacteria were isolated from traditional shrimp pond. These bacteria were NAS1, NAS2, and NAS3.  Based on the analysis of 16S rRNA gene sequence, NAS1 was identified as Breoghania sp., NAS2 identified as Pseudoalteromonas ruthenica, and NAS3 identified as Halomonas beimenensis. Ammonia reduction test showed that Halomonas beimenensis and Pseudoalteromonas ruthenica were able to reduce ammonia with a percentage of 8,4% and 20,3% for five days incubation. Therefore, these bacteria could be potential candidates as a bioremediation agent to improve water quality. Meanwhile, Breoghania sp. wasn’t show positive result in ammonia reduction test.